HISTOLOGICAL ANALYSIS OF LYMPHOID MASSES OF THE STOMACH AND SMALL INTESTINE IN THE CLINICAL AND PATHOGENETIC PROFILE OF BABESIOSIS - I. I. Torianyk (Проблеми екології та медицини)
Peripheral lymphoid organs respond immediately to a decrease in the body's defence responses, and their localisation and morphological specificity account for their active involvement in immunogenesis (especially in animals). This fact accentuates the morpho-functional estimation of the lymphoid tissue condition with the purpose of timely diagnostics of starting deviations and preventing the development of decompensated changes. Thus, the analysis of histological changes of the latter in natural and experimental prototypes of babesiosis is relevant. The aim of the research is to define the role of histological changes of lymphoid masses in the stomach and small intestine in the formation of the clinical and pathogenetic profile of babesiosis. We studied the structural changes of lymphoid masses of the stomach and small intestine in animals with babesiosis postmortem by histological methods. Fixation was traditionally carried out in 12% aqueous formalin solution, dehydration in alcohol (30º to absolute), and pouring (paraffin/ celloidin). Staining was conducted with eosin and haematoxylin, Van Gizon, Brasche. Analysis was performed using an Olympus BX-41 microscope, Japan (x 100; x 200; x 1350). Verification was carried out by cytological, ultramicroscopic, molecular genetic methods (polymerase chain reaction) and in a biological experiment on animals. Analysis of specimens of the lamina propria in the gastric mucosa of the animals in the experimental group and clinical observation group established that the latter contained diffuse accumulations of the lymphoid tissue. Their dispersal involved different parts of the organ, including quite large areas. Haematoxylin and eosin staining gave a clear histological pattern with a marked contrast of fragments, which contributed to diagnostic resources. Lymphoid follicles were observed occasionally, their marginal, mantle zones were blurred. The germinative centres were not detected and did not show any lucency. Neutrophilic granulocytes, monocytes and plasma cells predominated among the cellular leucocyte populations. Examination of the lymphoid apparatus of the small intestine showed predominantly diffuse nodular hyperplasia, which was widespread. A focal version of the nosological prototype was observed in individual specimens occasionally, presented as single cells (most often in the terminal parts of the organ). Histological changes of lymphoid masses of the stomach and small intestine in animals with babesiosis consisted in the development of expressive diffuse nodular hyperplasia with disorganization of the structure of lymphoid follicles, destruction of zonality of the latter, making it impossible to detect germinative centres.